Exploration of Personality Factors and their Effects on People's Decision Making of Complementary and Alternative Medicine - Praheli Dhar Chowdhuri; Suman Meyur (International Journal of Management Studies, 2018)
Complementary and Alternative medicine (CAM) often promoted and utilized as a non-integral part of conventional medicine has diverse modalities and variegated application. To choose among the alternatives in a comparable situation the decision process is complex and dependent on many factors including social, cognitive component and personality traits. This study is aimed to explore whether the factors affecting the choice of treatment modality between CAM and Conventional Medicine has any underlying effects of personality of the decision makers, as per Big 5 personality traits. The study focuses on the decision making process behind the choice of therapy so that a valid decision path can be formulated. It was found that Personality has an important role in decision making as three underlying Personality Factors (Neuroticism, Conscientiousness and Extraversion) are separately identified. Extraversion has positive (B = 0.693, p<0.001) and Conscientiousness has (B = -.306, p<0.001) negative effect. However, Neuroticism has no direct effect but affecting via one mediating component, i.e. Anxiety. Pro-CAM Social enabling factor is positively affecting CAM usage (B= .538, p<0.001). A validated path model has been constructed involving the effects of personality factors. This study shall help in future planning of healthcare human resource allocation, management as well as understanding the treatment seeker's psychosocial dynamics while making an important decision for attaining health.
Keywords: 330; Big 5 personality traits; Treatment decision making; CAM; Health human resource; Path analysis; Complimentary and alternative medicine